Exploring the Use of Mobile Learning in the Algerian EFL Context. Case of Ibn Khaldoun University of Tiaret. Algeria. - lahmer, moktaria (Journal of Social Sciences and Humanities, 2021)
In the current globalized world, mobile -assisted language learning (MALL) is witnessing a rapid advance inspired from contemporary technology. Hence, technology being a tool utilized for the purpose of learning and teaching. It is regarded as a new field of educational technology. Nowadays, this trend is popular with students due to the widespread of various mobile technologies to enhance learning. The present study attempts to explore the attitudes of EFL learners as well as teachers towards the effectiveness of using mobile- assisted techniques in language learning. For this purpose, the researcher used a questionnaire to elicit the respondents’ responses. The data collection phase involved students of various levels at the English section at Ibn Khldoun University of Tiaret.The results unveiled that students of English have positive attitudes towards the effectiveness of M-learning. Students reported considering M-learning as a useful technique in improving the four main skills as well as their cultural knowledge. They demonstrated willingness to adopt the technique in their learning despite the skeptical views about their teachers’ ability to orchestrate this significant shift. Results also concluded that teachers regardless of their positive attitudes are more concerned about the infrastructure and the proper guidance needed to implement such a technique in reality. Overall, this study aims to explore to which extent the EFL context at Ibn Khaldoun University is willing and ready to adopt technology in language classrooms. Similarly, it attempts to find out how accepting is the EFL context to follow the globalized world in its race for technology-based classrooms.